(untitled) (Politeja, 2015)
Two Crises and a Revolution: 2004 and 2014 Events in Ukraine in Comparative Perspective Why has V. Yanukovych been long able to survive while L. Kuchma failed? This paper seeks to locate the factors leading to the quick downfall of the Kuchma’s regime in Ukraine in 2004 in comparison to the extended regime survival in 2014. Drawing on the political science theories of dynamics of hybrid regimes and revolution, the author advances two theses: first, the mass mobilization is necessary but not a sufficient condition for the collapse of an autocrat. Comparing the two crisis episodes of 2004 and 2014 in Ukraine by using ten indicators, the author argues that the regime’s organizational capacity initially was higher than both Western democratic pressure and “people’s power”. Only after the third violent attempt to disperse Maidan had failed, the “power vertical” collapsed what led to the creation of a new parliamentary majority and effective loss of power by the incumbent. Second, unlike the crisis of 2004 the crisis of 2014 has not been resolved through the compromise and turned into a revolution. Applying eleven, analytically defined, attributes of the revolution to the Orange events of 2004 resulted only in three matches, while in 2014 there are already seven matches (breakdown of the state, international pressure, economic decline, conflict between elites, mass mobilization, “multiple sovereignty” and violence) and two others (the change of regime and the change of social structure) is theoretically possible. The presence of these attributes suggests that in 2014 Ukraine had a political, but could hardly have a social revolution.